Adult Re-entry Education Barriers in Likasi: Institutional Challenges Analysis - Subhashini, Robin; Dorathy, Ghosh Anne; Dilip, Ajit Kaur (Journal of Educational Research and Policies, 2026)
The objective of this work is to show the reasons that push people of advanced age to return to school to strengthen or broaden their scientific skills. This work also shows the difficulties that adults face when they return to school.